ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI DITINJAU DARI EMPOWERMENT, SELF EFFICACY DAN KEPUASAN KERJA - I Made Sunata; Anak Agung Ketut Sri Asih (Forum Manajemen STIMI Handayani Denpasar, 2015)
Human resources in an organization has a very important role, becausewithout the support of a good human resources of an organization will faceproblems in achieving organizational goals. Someone who has the empowermentand self-efficacy is high, and feel satisfaction in working of course he would workas closely as possible with all the capabilities to provide the best performanceto the organization where he worked with the task of completing the work aspossible. In fact, employees who are satisfied will have the willingness to do morebeyond their formal responsibilities. Willingness is then known as organizationalcitizenship behavior (OCB). Dishubkominfo who becomes the object of this studyis one of the local government agencies in Badung. This study aims to determinethe effect of empowerment, self-efficacy, and job satisfaction on organizationalcitizenship behavior (OCB). This study uses primary data obtained from the resultsof questionnaires. Results of multiple linear regression analysis showed: 1) thereis positive but not significant empowerment of the OCB, 2) there is a positive andsignificant impact on OCB self efficacy, 3) there is a positive and significant impacton OCB job satisfaction, 4) there is positive and significant empowerment, selfefficacy,and job satisfaction of the OCB, 5) the level of influence that contributedempowerment, self-efficacy, and job satisfaction on OCB 41.3% and the remaining58.7% is influenced by other variables.